HOW TO REDUCE STROKE RISK IN CLINICAL PRACTICE - O. M. Drapkina; N. P. Musina; V. T. Ivashkin (Российский кардиологический журнал)
Even though the problem of stroke is actively discussed in journals, monographs, conference presentations, etc., it is still unresolved, pointing to the need for more effective strategies on reducing stroke mortality, morbidity and disability. Stroke is a multifactorial disease, asking for multidisciplinary approaches in complex risk factor assessment and individual prevention programme development.